2021
DOI: 10.1159/000517851
|View full text |Cite
|
Sign up to set email alerts
|

Higher Levels of C-Reactive Protein and Ferritin in Patients with Overweight and Obesity and SARS-CoV-2-Related Pneumonia

Abstract: <b><i>Introduction:</i></b> Overweight and obesity are associated with a more severe COronaVirus Disease 19 (COVID-19). Adipose tissue-related chronic inflammation could be a promoter for the occurrence of the cytokine storm that predicts aggravation of COVID-19. The primary aim was to investigate if this increased risk for more severe COVID-19 was associated with a higher inflammatory response. <b><i>Methods:</i></b> We enrolled patients &#x3c;75 years old h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…However, inflammation is exacerbated more by hyperlipidemia and obesity, particularly in COVID-19 patients [ 28 ]. Non-survivors displayed elevated serum C-reactive protein, ferritin, and IL-6 levels upon hospital admission [ 29 , 30 ]. The intravenous administration of CIGB-258 (1 or 2 mg for every 12 h) showed the therapeutic potential to treat hyperinflammation of patients with COVID-19 with a remarkable decrease in cytokine levels present in “cytokine storm”, such as IL-6 and TNF-α [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, inflammation is exacerbated more by hyperlipidemia and obesity, particularly in COVID-19 patients [ 28 ]. Non-survivors displayed elevated serum C-reactive protein, ferritin, and IL-6 levels upon hospital admission [ 29 , 30 ]. The intravenous administration of CIGB-258 (1 or 2 mg for every 12 h) showed the therapeutic potential to treat hyperinflammation of patients with COVID-19 with a remarkable decrease in cytokine levels present in “cytokine storm”, such as IL-6 and TNF-α [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…This could be one of the factors explaining the worse severity and outcome seen in such a population. Similarly, a retrospective study showed that maximal CRP and ferritin levels during hospitalization were higher in obese than normal-weight COVID-19 patients [ 46 ]. Other markers of severity, including D-dimer, LDH, CRP, and ESR, were higher in obese patients in our study but were statistically insignificant.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, severe CoVID-19 has been associated with lower expression of IFN-γ by CD4 + , an antiviral protein [ 97 ]. It was demonstrated that patients with obesity and overweight presented higher levels of CRP and ferritin than patients with normal weight, in a CoVID-19 medical ward, whereas IL-6 levels were higher in all the subjects [ 98 ].…”
Section: Obesity Covid-19 and Low-grade Inflammation: Molecular Insightsmentioning
confidence: 99%